Neopulvinaria innumerabilis (Rathvon, 1854), a new species of Coccidae in Serbia - Dervišević, Marina; Graora, Draga (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2024)
In 2016, the species Neopulvinaria innumerabilis (Rathvon, 1854), belonging to the scaleinsect family Coccidae, was for the first time found in Serbia, in the location Radmilovacon Cornus sanguinea L. It reproduces by gamogenesis, develops one generation annually,and overwinters as a fertilized female on the trunk or branches of its host plant. During thisresearch, the species was detected on five host plants at six locations in Serbia. It feeds bysucking sap from leaves, young shoots and branches of infested plants, causing desiccation ofleaves and individual twigs. Four species of its natural enemies were collected and reared fromcolonies of N. innumerabilis. Two species of parasitoid wasps, Coccophagus lycimnia (Walker)(Aphelinidae) and Metaphycus hageni Daane and Caltagirone (Encyrtidae), were found, whilethe ladybird Exochomus quadripustulatus L. (Coccinellidae) and the fly Leucopomyia silesiaca(Egger) (Chamaemyiidae) were identified as predators. The most abundant entomophagousspecies was L. silesiaca.
Keywords: cottony maple scale; Coccidae; natural enemies; Serbia